A qualitative study on shared decision‐making of patients with chronic kidney disease - Ya‐Fang Ho; Yu‐Chi Chen; I‐Chuan Li (Wiley, 2021)
Abstract Aim This study aims to explore the change process among chronic kidney disease patients in shared decision‐making. Design Qualitative research is the design applied. Method Original transcripts from an earlier study involving a purposive sample of 31 patients with chronic kidney disease provided a source of information. The data collection was conducted from August 2017-January 2018. Data analysis applied the thematic analysis method. Results Three themes were identified: from avoidance to being forced to accept, decision‐making process of action and facilitating factors. After making the psychological adjustments necessary for undergoing dialysis treatment, participants experience the process of decision‐making action. The improvement of knowledge and ability increases the patient's self‐determination consciousness and strengthens confidence in decision‐making. The nurse and the patient's family are both important facilitating factors, and they assist through the entire SDM process.